SELF DEFENSE MECHANISM SEBAGAI STRATEGI BIMBINGAN MENTAL SPIRITUAL BAGI PECANDU NARKOBA TEMBAKAU GORILLA - Zaen Musyrifin; Nur Arifin Setiawan (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2020)
This study discussed the self defense mechanism for former gorilla tobacco users to stop using gorilla tobacco and not to take drugs again. The purpose of this research was to get an overview of self defense mechanism of former gorilla tobacco users that can be developed as a spiritual mental guidance strategy. The focus of this research is the forms of self defense mechanism, namely repression, displacement, projection, denial, introjection, regression, sublimation, reaction formation, and identification. This research used qualitative research method with case study.